The empire of the cities : emperor Charles V, the comunero revolt, and the transformation of the Spanish system - Espinosa, Aurelio (Studies in medieval and Reformation traditions, 2009)
Starting in the nineteenth century the scholarly consensus has been to attribute the decline of the Spanish empire to structural rigidity, corrupt bureaucracy and repressive policies. In ""The Empire of the Cities, "" Aurelio Espinosa challenges these theories and offers groundbreaking insight into Spain's political process and emphasizes early modern state formation. Spain's empire should no longer be viewed simply as a symbol of royal absolutism and dominance. Rather it functioned as a collection of autonomous municipalities interconnected by a parliament that articulated domestic programs an.